International bean rust nursery: results 1977-1978 - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1979)
The International Bean Rust Nursery (IBRN) is in charge of testing promising Phaseolus vulgaris cv. and lines for their resistacne to rust (Uromyces phaseoli). In 1975-76 132 bean lines were tested, among which there were 28 potential rust-race differentials. In 1977-78, 26 trials were planted with the help of 20 collaborators in 22 locations of L.A., U.S.A., Europe, Africa and Australia. Rust incidence was evaluated 20-40 days after planting and 40-60 days after germination, according to the intensity of infection and type of pustule that can be found at any of the 5 stages of development. The final classification of the plant`s reactions to each material at the different sites is given in table form. Var. Cocacho (4), Cuilapa 72 (26), Redlands Pioneer (28), Redlands Greenleaf B (44), Redlands Greenleaf C (46) and Puebla 87 (88) did not show susceptibility at any of the locations. (AS)